The old faith and the Russian land: a historical ethnography of ethics in the Urals - Rogers, Douglas (Culture and society after socialism, 2009)
In search of salvation on the Stroganov estates -- Faith, family, and land after emancipation -- Youth : exemplars of rural socialism -- Elders : Christian ascetics in the Soviet countryside -- New risks and inequalities in the household sector -- Which khoziain? Whose moral community? -- Society, culture, and the churching of Sepych -- Separating post-Soviet worlds? : priestly baptisms and priestless funerals